ANALISIS MASALAH PEMBUDIDAYA IKAN NILA DI DESA TANAH PERIUK I DAN DESA AIR SATAN - Rudiansyah Rudiansyah; Sri Murtini; Neksidin Neksidin (Jurnal Perikanan Darat dan Pesisir (JPDP), 2020)
Fish farming is an aquaculture activity to maintain fish from larvae to become economic size with providing profit and maintaining of fish population. Analysis of the problems faced by tilapia in the flowing pond system needs to be carried out because it will focus on solving problems. In this study, the analysis used was descriptive qualitative method, where the data came from respondents who were entrepreneurs of tilapia farming. The data obtained from the interviews were divided into three theme groups, first, a discussion of water sources, second, concerning cultivation systems, third, concerning market and capital. The results indicate that the source of cultivated water has no significant problems, some respondents stated that the watervang dam irrigation water source was closed for repair in 2018 for five months, it was stopped for one cycle of tilapia farm activation. The aquaculture system used is still a traditional system with little technology used, the main problem is feed price and the monopoly carried out by "Bos Pakan". The average respondents is owning pond or workers, they just buy tilapia fingerling, when feed and the market is regulated by the partner “boss of feed. This condition make selling price of fish and the price of feed can monopolized by partner “bos pakan”. Suggestion is needs regulation from governments to manage this problem.